Application of deep convolutional neural network in breast cancer prediction using Digital Mammograms - Al Mamun, Rafsan; Rafin, Gazi Abu; Alam, Adnan; Sefat, MD. Al Imran (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.